Moderasi Kepuasan Pelanggan atas Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan Ojek Online di Kota Kendari - Baladin, La Ode; Soeparyanto, Try Sugiyarto; Fidmasari, Rezki; Satyadharma, Maudhy; Hado (Jurnal Bisnis dan Kewirausahaan, 2025)
This study aims to test and analyze the mediating role of customer satisfaction on customer loyalty in the context of Grabbike services in Kendari City. This study is important for application providers, especially in responding to the challenges of online transportation competition, especially online motorcycle taxis. In addition, for the government, this study is an input in formulating urban transportation planning based on community needs. This study involved a population of 160 respondents who used Grabbike services in Kendari City. and used the Structural Equation Model (SEM) to test the hypothesis. The results showed that service quality has a positive and significant effect on customer loyalty and satisfaction. In addition, customer satisfaction is proven to have an effect on loyalty, while price does not have a significant impact.